2003
DOI: 10.1021/ol034632c
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization at C-12 of 1α,25-Dihydroxyvitamin D3 Strongly Modulates the Affinity for the Vitamin D Receptor (VDR)

Abstract: The first synthesis of analogues of the natural hormone 1alpha,25-dihydroxyvitamin D(3) (1a) with substituents at C-12 is reported. The following are the relative affinities of the novel compounds for the vitamin D receptor (VDR) compared to that of 1a (100%): 1alpha,12alpha,25-(OH)(3)-D(3) (1b, 1%), 1alpha,25-(OH)(2)-12-methylene-D(3) (1c, 50%), and 1alpha,25-(OH)(2)-12beta-methyl-D(3) (1d, 440%). [structure: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Thus, it is possible that specific hydrophobic interactions between the VDR and the methyl groups of vitamin D analogs may play a role in calcemic activities of the vitamin D hormone. The biological importance of the vitamin 18‐methyl group/VDR contacts was recently suggested by Mourino 47. He showed that the introduction of different substituents at C‐12, which is close to the 18‐CH 3 group, dramatically changes the affinity of such hormone analogs for the VDR.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, it is possible that specific hydrophobic interactions between the VDR and the methyl groups of vitamin D analogs may play a role in calcemic activities of the vitamin D hormone. The biological importance of the vitamin 18‐methyl group/VDR contacts was recently suggested by Mourino 47. He showed that the introduction of different substituents at C‐12, which is close to the 18‐CH 3 group, dramatically changes the affinity of such hormone analogs for the VDR.…”
Section: Resultsmentioning
confidence: 98%
“…Triol 8a, precursor of the elongated triols 8b−c, would be prepared from the Inhoffen−Lythgoe diol (10) employing methodology developed in our laboratories. 12c, 14,22 The key triol intermediate 8a was prepared from the Inhoffen−Lythgoe diol (10) through the known unsaturated ketone 9 23 (Scheme 2). Reduction of ketone 9 with DIBAL-H followed by protection of the resulting allylic alcohol 11 with tert-butyldimethylsilyl chloride provided the silyl ether 12, which upon epoxidation from the less hindered face with mchloroperbenzoic acid gave epoxide 13 (82% over the three steps).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our strategy for the synthesis of analogues 2a − c was based on the convergent Wittig−Horner approach, which is based on the coupling of the anion of compound 3 (the phosphine oxide of ring A) with ketones 4a − c , which comprise the CD ring system and a C12-borne side chain (Scheme ). Ketones 4a − c would be obtained by attaching the appropriate side chain to the C12-ketone 5 , which would be prepared from the known alcohol 6 (itself obtained from commercially available vitamin D 2 ) , by methods recently developed in our laboratory 1 Retrosynthetic Analysis of Analogues 2 a − c …”
Section: Resultsmentioning
confidence: 99%
“…Ketones 4a-c would be obtained by attaching the appropriate side chain to the C12-ketone 5, which would be prepared from the known alcohol 6 (itself obtained from commercially available vitamin D 2 ) 16,18 by methods recently developed in our laboratory. 19 The preparation of compound 5 (Scheme 2) began with oxidation of 6 followed by R,β-unsaturation of the resulting ketone 7 by Saegusa's methodology. 20 Reduction of the resulting enone 8 provided the alcohol 9, which was protected as the silyl ether derivative 10.…”
Section: Resultsmentioning
confidence: 99%